2010
DOI: 10.1016/j.cplett.2010.08.052
|View full text |Cite
|
Sign up to set email alerts
|

On ultrasmall nanocrystals

Abstract: Ultrasmall nanocrystals are a growing sub-class of traditional nanocrystals that exhibit new properties at diameters typically below 2 nm. In this review, we define what constitutes an ultrasmall nanoparticle while distinguishing between ultrasmall and magic-size nanoparticles. After a brief overview of ultrasmall nanoparticles, including ultrasmall gold clusters, our recent work is presented covering the optical properties, structure, and application of ultrasmall CdSe nanocrystals. This unique material has p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
85
0
3

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(91 citation statements)
references
References 58 publications
3
85
0
3
Order By: Relevance
“…(McBride et al 2010;Kim et al 2014). Recent studies on the mechanism and dynamics of the photoluminescence (PL) of ultrasmall cadmium chalcogenide NPs (McBride et al 2010;Dukes et al 2011;Zhou et al 2011;Pennycook et al 2012;Rosson et al 2012), especially those performed on single NPs (Dukes et al 2011;Pennycook et al 2012), showed that the large spectral width of the PL band and relatively long PL life-time is not the result of the collective properties of an inhomogeneous NP ensemble but rather of inherent properties of each individual NP. These findings shed light and stimulated further discussions also on the PL mechanism in larger, ''regular'' NPs.…”
Section: Introductionmentioning
confidence: 99%
“…(McBride et al 2010;Kim et al 2014). Recent studies on the mechanism and dynamics of the photoluminescence (PL) of ultrasmall cadmium chalcogenide NPs (McBride et al 2010;Dukes et al 2011;Zhou et al 2011;Pennycook et al 2012;Rosson et al 2012), especially those performed on single NPs (Dukes et al 2011;Pennycook et al 2012), showed that the large spectral width of the PL band and relatively long PL life-time is not the result of the collective properties of an inhomogeneous NP ensemble but rather of inherent properties of each individual NP. These findings shed light and stimulated further discussions also on the PL mechanism in larger, ''regular'' NPs.…”
Section: Introductionmentioning
confidence: 99%
“…[38] The determination of the size of ultrasmall CdSe nanoparticle using tunnelling microscopy exposed to large margin error due to the very poor contrast. [39] Often local probes, such as high-resolution transmission electron microscopy (HRTEM) are used, but sometimes it is difficult to obtain accurate results on the average particle diameter or on the internal structure due to problems with sampling or poor contrast. The small-angle X-ray scattering (SAXS) analysis gives information about the shape and size of nanoparticles with good precision but contains no information about the atomic structure.…”
Section: Nanoparticle Size From Pdf Analysis: the Size Of Crystallinementioning
confidence: 99%
“…This obtained information is not available from some alternative conventional nano-techniques such as TEM. [39] Using this methodology, Yang et al [40] detected 'considerably enhanced compressive homogeneous strain and increased inhomogeneous strain in the bond-length distribution' of the first PDF peak, the latter reflecting the observed disorder of the ultrasmall nanoparticles. [40] This method is generally applicable to the characterisation of the nanostructured materials, many of which may exhibit complex structure.…”
Section: Introductionmentioning
confidence: 99%
“…Magic sized clusters of cadmium selenide have been documented in numerous recent reports and are believed to play crucial roles in nanocrystal synthesis, 111 including as a solute reservoir for larger nanocrystals and as building blocks for the assembly of sheet and ribbon structures. 1, 12 Many of these studies report a cluster with lowest energy absorption near 420 nm.…”
mentioning
confidence: 99%